Effects of D-norgestrel postcoital on the vaginal epithelium, cervical mucus and sperm penetration - Kesseru, Esteban (2015)
This study is part of a research program that focuses the action of postcoital d-Norgestrel on various parameters of the genital tract. We have studied the effects of a 0.4 mg tablet., Eaten in the ovulatory phase of the cycle, the colpocitograma, rheological properties of cervical mucus and intracervical and intrauterine sperm retrieval. The results were compared with those obtained in a control group without treatment.